Ta'lim Muta'allim: Solutions for Forming the Ta'dzim Attitude of Generation Z Students towards Teachers - Mar'atul Azizah; Akhmad Najibul Khairi Syaie (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This research aims to describe Ta'lim Muta'alim learning in the formation of Ta'dzim attitudes and Ta'dzim attitudes of students towards teachers at Mts Nurul Iman Dempok Grogol Diwek Jombang. The method used in this research is a qualitative method with a case study research design. Data collection techniques in this research were carried out using observation, interviews, and documentation methods. Testing the validity of the data was carried out by extending observations, increasing persistence, triangulation, using reference materials, peer discussions, and member checks. Data analysis techniques use data reduction, data presentation, and verification. This research produces the conclusion (2). The Ta'lim Al-Muta'allim teacher's efforts in forming a student's attitude of ta'dzim towards teachers at MTs Nurul Iman Dempok Jombang were carried out by preparing Expository Learning Strategies (SPE) and Inquiry Learning Strategies (SPI). Using printed learning media based on the Bald Bible and Al-Muta'allim Ta'lim Translation, lecture, deductive, bandongan, and sorogan methods are used. The formation of students' ta'dzim attitudes is carried out using two patterns, namely habituation and modeling. Students' attitude towards teachers at MTs Nurul Iman Dempok Jombang is characterized by respecting knowledge and teachers. Please do not walk in front of the teacher or bend when walking in front of him. Obeying the teacher's orders, namely helping the teacher clean the school environment, reading waqia'ah before Duha prayers, praying Duha prayers in congregation, folding carpets, and participating in activities related to the madrasah's vision and mission. This research provides recommendations to educational institutions and practitioners regarding the potential for developing more effective learning approaches for forming ta'dzim attitudes in Generation Z students.